Напрями підвищення конкурентоспроможності аграрного підприємства - Сітковська, Алла Олександрівна; Sitkovska, A.; Савенко, Олена Анатоліївна; Savenko, O.; Лебедєв, М. О.; Lebedev, M. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
Статтю присвячено стратегічним напрямам підвищення конкурентоспроможності аграрного підприємства. Розкрито сутність понять "конкуренції" та "конкурентоспроможність". Конкурентоспроможність підприємства, в тому числі аграрної галузі, розглядається через спектр системи, в якій вона залежить від ресурсного потенціалу конкурентоспроможності, який стоїть на початку дослідження та від цієї категорії стосовно кожної підсистеми виробничого осередку, їх взаємодії; від конкурентоспроможності виходу, тобто товару. Охарактеризовано чинники, що визначають рівень конкурентоспроможності аграрного підприємства, а також запропоновано узагальнену класифікацію факторів конкурентних переваг. Визначено методи оцінки рівня конкурентоспроможності підприємства. Для дослідження рівня конкурентоспроможності аграрного підприємства обрано методику, в основі якої є виявлення головних чинників і виділення групи показників, які в сукупності дозволять отримати характеристику рівня забезпечення їм конкурентних переваг. Для дослідження довгострокових перспектив управління конкурентоспроможністю С(Ф)Г "Росава" використано метод бенчмаркінгу, який розглядається як система посилення конкурентоспроможності господарської діяльності аграрного підприємства. The article is devoted to strategic directions of increasing the competitiveness of agrarian enterprise. The essence of the concepts of "competition" and "competitiveness" is revealed. The competitiveness of an enterprise, including the agrarian sector, is considered through the spectrum of the system in which it depends on the resource potential of competitiveness that stands at the beginning of the study and on the given category for each subsystem of the production unit, their interaction; from the competitiveness of the output, ie the product. The factors that determine the level of competitiveness of agrarian enterprise are characterized, as well as a generalized classification of factors of competitive advantage. The methods of estimation of the level of competitiveness of the enterprise are determined. To study the level of competitiveness of agrarian enterprise, a methodology was chosen, based on the identification of the main factors and the allocation of a group of indicators, which together will allow to obtain a characteristic of the level of providing them with competitive advantages. To study the long-term prospects of managing the competitiveness of Rosava, we used the benchmarking method, which is considered as a system of enhancing the competitiveness of agrarian enterprise's economic activity. For Rosava, the component of production potential is its investment and innovation potential, which is a constant priority of planning and improvement in the production center. The level of development and prospect of growth of investments in agrarian production and management of economic activity characterizes the ability of the enterprise to accumulate and attract investment funds in agro-innovative projects in order to achieve a high competitive level. For the economy, the question of the development of this particular component of the economy is acute, since it is now quite low (investment attractiveness). Although certain measures in this direction in the economy are implemented and planned for the long term, namely: development, introduction of new elements of fixed capital and modernization of existing ones, improvement of production technologies to bring the enterprise to a new stage of development.
Areas of improving competitiveness of agrarian enterprise
А. О. Сітковська ORCID: 0000-0003-1892-6314 О. А. Савенко ORCID: 0000-0002-2362-6263
Keywords: аграрне підприємство; agrarian enterprise; конкурентоспроможність; competitiveness; стратегія; strategy; конкурентні позиції; competitive positions; бенчмаркінг; benchmarking